The role of Hippo‐YAP signaling in squamous cell carcinomas. Issue 1 (9th December 2020) - Maehama, Tomohiko; Nishio, Miki; Otani, Junji; Mak, Tak Wah; Suzuki, Akira
Abstract: The Hippo‐YAP pathway regulates organ size, tissue homeostasis, and tumorigenesis in mammals. In response to cell density, external mechanical pressure, and/or other stimuli, the Hippo core complex controls the translocation of YAP1/TAZ proteins to the nucleus and thereby regulates cell growth. Abnormal upregulation or nuclear localization of YAP1/TAZ occurs in many human malignancies and promotes their formation, progression, and metastasis. A key example is squamous cell carcinoma (SCC) genesis. Many risk factors and crucial signals associated with SCC development in various tissues accelerate YAP1/TAZ accumulation, and mice possessing constitutively activated YAP1/TAZ show immediate carcinoma in situ (CIS) formation in these tissues. Because CIS onset is so rapid in these mutants, we propose that many SCCs initiate and progress when YAP1 activity is sustained and exceeds a certain oncogenic threshold. In this review, we summarize the latest findings on the roles of YAP1/TAZ in several types of SCCs. We also discuss whether targeting aberrant YAP1/TAZ activation might be a promising strategy for SCC treatment. Abstract : We summarize the latest findings on the roles of YAP1/TAZ in several types of SCCs, proposing that many SCCs initiate and progress when YAP1 activity is sustained and exceeds a certain oncogenic threshold.